2010
DOI: 10.4141/cjps10006
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of legume cover crop-winter wheat intercrops on the semi-arid Canadian Prairies

Abstract: . 2010. Suitability of legume cover crop-winter wheat intercrops on the semiarid Canadian prairies. Can. J. Plant Sci. 90: 479Á488. Farmers on the Canadian prairies are interested in including legume cover crops in their cropping systems to reduce fertilizer inputs and improve farm sustainability. A field study was conducted to determine the merits of establishing alfalfa (Medicago sativa L.), red clover (Trifolium pratense L.) or Austrian winter pea (Pisum sativum L.) cover crops in fall or in spring with win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…Yield benefits to the subsequent crop were observed in all studies in treatments where legumes established and grew successfully. Blackshaw et al (2010) also observed weed suppression by the alfalfa cover crop.…”
Section: Cover Cropsmentioning
confidence: 86%
See 2 more Smart Citations
“…Yield benefits to the subsequent crop were observed in all studies in treatments where legumes established and grew successfully. Blackshaw et al (2010) also observed weed suppression by the alfalfa cover crop.…”
Section: Cover Cropsmentioning
confidence: 86%
“…In Alberta, red clover, alfalfa, and winter pea (Pisum sativum L.) were established successfully with winter cereals in both fall and spring plantings (Blackshaw et al 2010). In all these studies, biomass production by cover crops varied widely, ranging from near 0 to over 4000 kg ha (1 .…”
Section: Cover Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a number of integrated weed management studies in south-central Alberta incorporating cover crops, underseeding and green manures [35][36][37][38][39]. While all of these studies included some form of chemical management in the protocol, all related their work to potential for organic systems.…”
Section: Weed Managementmentioning
confidence: 99%
“…The authors suggest that some of the weed suppression effect of sweetclover may have been due to allelopathic compounds. Alfalfa, red clover, or Austrian winter pea were grown as spring or winter planted cover crops in dryland systems of the western Prairies [37]. Spring planted legumes exhibited limited growth, and there were some problems associated with winter kill, crop yield suppression and/or weed control, with all cover crops except alfalfa.…”
Section: Weed Managementmentioning
confidence: 99%